Determinan Kemiskinan Multidimensi Indonesia Wilayah Timur Tahun 2015-2021 - Khofifah Oktharen; Dwirani Puspa Artha (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the determinants of multidimensional poverty in eastern Indonesia during the period 2015–2021. The approach used is quantitative with panel data regression method, utilizing secondary data from Statistics Indonesia (BPS) and The Prakarsa. The variables analyzed include the open unemployment rate, high school completion rate, life expectancy, and slum area level on the multidimensional poverty rate (AKM) in 13 provinces. The estimation results show that the high school completion rate and life expectancy have a negative and significant effect on multidimensional poverty, while the open unemployment rate and slum area have no significant effect. This finding confirms that increasing access to and quality of secondary education and improving public health are key factors in reducing multidimensional deprivation in eastern Indonesia. The implications of this study highlight the importance of integrated development policies, not only focusing on increasing income, but also needing to be directed at strengthening community capabilities through inclusive education and health as the main strategy for alleviating multidimensional poverty. Keywords: multidimensional poverty, unemployment, education, life expectancy, slums